Peningkatan Literasi Digital dan Etika Bermedia Sosial Bagi Santri Dayah Darul Muta'alimin - Jauharil Maknuni; Ishaq (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The rapid development of information technology has transformed the way people live, including how they communicate and interact socially. Social media has become one of the main platforms for individuals, including students at Islamic boarding schools (santri), to communicate and access information. However, not all social media users possess adequate digital literacy, making them vulnerable to the spread of misinformation (hoaxes) and negative behaviors. Therefore, improving digital literacy and understanding social media ethics is crucial, especially for santri in pesantren. The program